Inovasi Website Sipenduk Online dalam Upaya Percepatan Pelayanan Administrasi Kependudukan di Desa Dasun Kecamatan Lasem - Ony Vena Mulyana; Dandy Patrija W; Nihayatus Sholicah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study discusses the implementation and impact of the Sipenduk Online system in Dasun Village as part of the digital transformation of population administration services. The purpose of this system is to accelerate and improve the accessibility of public services at the village level. In the era of e-government, this system is a response to various challenges of conventional services such as long queues, slow processes, and geographical barriers. The research method used is qualitative, with data collection techniques through in-depth interviews and direct observation. The results of the study show that Sipenduk Online has a positive impact, such as the efficiency of the administrative process, increased transparency, and ease of access to services without the need for physical presence. The real-time application tracking feature also increases public trust in the system. In addition, the flexibility of time in submitting documents is very helpful for residents with limited mobility. However, several challenges are still encountered, including limited internet infrastructure, low digital literacy among the elderly, and technical glitches in the notification feature. Therefore, it requires upgrading of technological infrastructure, community training, and sustainable system development. Support from the village government and active participation of the community are the keys to the success of this system. The study concludes that the digitalization of public administration in villages can encourage the creation of more responsive and inclusive governance, while contributing to improved service quality, data accuracy, and better development planning.